WAVEFORM CLASSIFICATION OF VOLCANIC LOW-FREQUENCY EARTHQUAKE SWARMS AND ITS IMPLICATION AT SOUFRIèRE HILLS VOLCANO, MONTSERRAT - Green D.N.; Neuberg J. (My University, 2006)
Low-frequency volcanic earthquakes are indicators of magma transport and activity within shallow conduit systems. At a number of volcanoes, these events exhibit a high degree of waveform similarity providing a criterion for classification. Using cross-correlation techniques to quantify the degree of similarity, we develop a method to sort events into families containing comparable waveforms. Events within a family have been triggered within one small source volume from which the seismic wave has then travelled along an identical path to the receiver. This method was applied to a series of 16 low-frequency earthquake swarms, well correlated with cyclic deformation recorded by tiltmeters, at Soufrière Hills Volcano, Montserrat, in June 1997. Nine waveform groups were identified containing more than 45 events each. The families are repeated across swarms with only small changes in waveform, indicating that the seismic source location is stable with time. The low-frequency seismic swarms begin prior to the point at which inflation starts to decelerate, suggesting that the seismicity indicates or even initiates a depressurisation process. A major dome collapse occurred within the time window considered, removing the top 100 m of the dome. This event caused activity within some families to pause for several cycles before reappearing. This shows that the collapse did not permanently disrupt the source mechanism or the path of the seismic waves. © 2005 Elsevier B.V. All rights reserved.
Keywords: CLASSIFICATION; CROSS-CORRELATION; LOW-FREQUENCY EARTHQUAKES; MONTSERRAT; SWARMS; VOLCANO; WAVEFORM